2021
DOI: 10.3390/en14112986
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation of Biodiesel Blends with the Common Rail Diesel Engine’s Performance and Emission Characteristics

Abstract: The use of biofuel has been researched and announced by scientists to bring benefits in terms of environmental protection. However, studies continue to be conducted to achieve stable results and confirm biofuels as an effective alternative fuel for internal combustion engines. In this study, the fuel used is biodiesel derived from fish oil and conventional diesel fuel. Specifically, the test fuel is conventional diesel mixed with fish oil biodiesel in different ratios, including B0, B10, B20, B30, B40, and B50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…AVL Boost software was able to simulate almost all combustion engine types: SI engines, 24 26 CI engines, 27 turbocharged engines, 28 and alternative fuel engines. 29 , 30 …”
Section: Experimental System and Engine Modelingmentioning
confidence: 99%
“…AVL Boost software was able to simulate almost all combustion engine types: SI engines, 24 26 CI engines, 27 turbocharged engines, 28 and alternative fuel engines. 29 , 30 …”
Section: Experimental System and Engine Modelingmentioning
confidence: 99%
“…For an engine in perfect condition, HC values decline as the revolutions per minute (rpm) rise, indicating that the supply system economizes appropriately, either in a carburettor or fuel injection system. 46 In the present study is observed that at medium speeds (1500–2000 rpm), there is a minimum in the HC emissions with an average reduction of about 27.7% compared with diesel fuel at any speed rating, Fig. S12 †.…”
Section: Resultsmentioning
confidence: 52%
“…As the calorific value was lower, the total amount of heat gained during combustion was reduced, and thus the amount of successfully converted heat was reduced. Because of the decrease in combustion delay, due to the higher cetane number of the biodiesel fuel, the mixture ignited faster, and the phenomena of both combustion and compression occurred when using bio-fuel, resulting in reduced power [20][21][22].…”
Section: The Effect Of Biodiesel Blendsmentioning
confidence: 99%
“…As the calorific value was lower, amount of heat gained during combustion was reduced, and thus the amount cessfully converted heat was reduced. Because of the decrease in combustion de to the higher cetane number of the biodiesel fuel, the mixture ignited faster, phenomena of both combustion and compression occurred when using bio-fuel ing in reduced power [20][21][22]. The results show that, at all load modes, the capacity of B0 was the highest ally decreased when the biodiesel mixing ratio increased, and reached its lowest with B50 fuel.…”
Section: The Effect Of Biodiesel Blendsmentioning
confidence: 99%